A study on the influence of dose rate on total ionizing dose effect of anti-fuse field programmable gate array—The irradiation damage is attenuated at low dose rate - Liu, Minqiang; Xu, Xianguo; Zeng, Chao; Xiong, Cen (Frontiers in Physics, 2022)
The TID (total ionizing dose) in-situ experiments of LC1020B, an anti-fuse FPGA (Field Programmable Gate Array) device, were designed and carried out under different dose rates, and the influence of dose rate on the TID effect of FPGA was studied. The experimental results show that: 1) the TID irradiation failure of the FPGA under different dose rates has nothing to do with the input voltage parameter exceeding the standard. 2) with the decrease of cobalt source irradiation dose rate [171, 26.83, and 2.68 mGy(Si)/s], the TID effect failure dose threshold [168, 229, and 334 Gy(Si), respectively] of the FPGA gradually increased, showing obvious attenuation of low dose rate damage. Theoretical analysis suggests that, compared with the space charge limitation effect, the oxide charge annealing effect plays a dominant role, and longer irradiation time is beneficial to the oxide charge annealing. And based on the experimental data, an FPGA TID analytical model with power consumption current as the damage characterization parameter is established, which lays a foundation for scientific evaluation of radiation effect of anti-fuse FPGAs.